COMPARISON OF THE EXPRESSION OF SEXUAL DEVELOPMENT AND ITS DELAY IN ADOLESCENT GIRLS IN DIFFERENT REGIONS - Bekbaulieva Gulistan Nietbaevna; Ibrahimova Nodira Otabekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Clinical signs of mental retardation are accompanied by physical development disorders: a decrease in BMI and deviations in the formation of the skeletal system. With an increase in the deficiency of sexual development, the frequency of the nomothetic body type decreases, and disproportions in the development of the chest and bone pelvis increase. In adolescents with mental retardation against the background of signs of sexual infantilism, the following secondary menstrual disorders are detected: secondary amenorrhea - in 22.9%, opsomenorrhea - 43.1%, long-term (more than two years), menstrual cycles are established - 34.0%, of which accompanied by juvenile bleeding - 9.2%. According to the developed prognostic scale of risk factors for mental retardation in girls, the most important are a decrease in BMI, later menarche in the mother or close relatives, and chronic stressful situations. Calculation of an individual risk index makes it possible to predict the likelihood of developing a disease in the prepubertal and early puberty periods and to determine the necessary therapeutic and preventive measures.